Does Economic Freedom Matter to Foreign Direct Investment in Sub-Saharan Africa? - Sooreea-Bheemul, Brinda; Rasool, Uzma Shataz; Sooreea, Rajeev (International Journal of Economics and Financial Issues, 2020)
This paper examines whether economic freedom matters to inward Foreign Direct Investment in Sub-Saharan Africa. A key contribution of this study is that it uses disaggregated measures of economic freedom from the Heritage Foundation and the Fraser Institute to unveil which components of economic freedom matter for inward FDI in a sample of 40 SSA countries during the 1997-2016 period. The estimation is done using panel data models with fixed and random effects. The results indicate that higher overall economic freedom is a key determinant of inward FDI in SSA. However, there is clear evidence that it is regulatory efficiency (business, labor and monetary freedom), fiscal freedom (low tax burden), market openness, market size, trade openness, and strong telecommunications infrastructure that are the key factors in attracting FDI in SSA. While monetary freedom (price stability) is important, financial freedom (banking and financial sector independence) or investment freedom seem less critical. Results on trade freedom suggest that SSA tends to attract tariff-jumping and efficiency-seeking FDI. There is no consistent evidence that stronger rule of law and property rights really matter for inward FDI in SSA. It appears that FDI tends to flow to SSA countries that have lax property rights protection. Keywords: Foreign Direct Investment, Economic Freedom, Sub-Saharan Africa JEL Classifications: C33, F21, O43, N27 DOI: https://doi.org/10.32479/ijefi.9597